L-carnitine and alpha-lipoic acid fail to improve anaerobic and aerobic performance in trained cyclists despite a reduction in blood lactate concentration - de Rozas, A.; Pérez-Díaz, J.; Muros, J.; Sánchez-Muñoz, C.; Rufían-Henares, J.; Zabala, M.; Salas-Montoro, J. (Nutrients, 2025)
Background/Objectives: This study aimed to evaluate the effects of four weeks of combined Acetyl-l-Carnitine and alpha-lipoic acid (ALA) supplementation on anaerobic and aerobic performance and fatigue resistance in trained cyclists, hypothesizing improvements in maximal aerobic power (MAP), Wingate test performance, and reduced lactate accumulation.